2017
DOI: 10.7863/ultra.16.05059
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Length in Patients at Risk for Placenta Accreta

Abstract: Women with placenta accreta had shorter cervical lengths at 32 to 34 weeks than women with a nonadherent low-lying placenta or placenta previa, but this finding did not correlate with a higher risk of vaginal bleeding or preterm labor resulting in preterm birth before 36 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There is some correlation with cervical length and the risk of preterm birth with previa (less likely with a longer cervix) (41e43), but cervical length has not been extensively evaluated in placenta accreta spectrum. One small study noted no increase in the risk of preterm birth with short cervix and accreta (44). Placenta previa is not a contraindication to transvaginal ultrasonography, and ultrasound examination may provide important information about placenta accreta spectrum and previa in addition to cervical length (35).…”
Section: Obstetric Care Consensusmentioning
confidence: 99%
“…There is some correlation with cervical length and the risk of preterm birth with previa (less likely with a longer cervix) (41e43), but cervical length has not been extensively evaluated in placenta accreta spectrum. One small study noted no increase in the risk of preterm birth with short cervix and accreta (44). Placenta previa is not a contraindication to transvaginal ultrasonography, and ultrasound examination may provide important information about placenta accreta spectrum and previa in addition to cervical length (35).…”
Section: Obstetric Care Consensusmentioning
confidence: 99%
“…[12] A previous ultrasound study showed that women with IPP had shorter cervical lengths at 32 to 34 weeks than women with a non-adherent low-lying placenta or placenta previa. [21] Our results showed that patients with the S2 involvement had shorter cervical lengths than the patients with the S1 invasion. Measurement of cervical lengths could help to depict the S2 invasion and increase the accuracy of topographic evaluation.…”
Section: Discussionmentioning
confidence: 62%
“…35 Rather than having an arbitrary gestational age, some authors have advocated for an individualized and patient-specific risk dependent approach. [36][37][38] 39,40 The authors acknowledge that individualized and patient-specific risk decision analysis are often part of this complex decision process; additional data are needed to further inform on this area.…”
Section: Discussionmentioning
confidence: 99%